Telaah Prinsip Good-Relationship di Dalam Kepemimpinan dan Organisasi - Zaluchu, Sonny Eli; Waruwu, Mesirawati (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2020)
AbstractThis research was conducted with a literature study that utilizes concepts, theories, and explanations from primary sources in books, journal papers, and other academic sources. The analysis presented descriptively to explore the principle of